BERTEKUN DALAM IMAN MENURUT KITAB IBRANI 12:1-3 - Tulus Raharjo; Riko Marga (Jurnal Pistis: Teologi dan Praktika, 2021)
The maturity of the Christian faith is shown through faithfulness in faith and perseverance in following the teachings of the Bible. The letter to the Hebrews is one of the letters that anticipates the potential apostasy of the Jewish Christians. Some commentators misunderstand Hebrew’s letter theology through inadequate interpretation. The discussion of the concept of apostasy has influenced the interpreters in concluding his theory. The concept of the unity of faith and perseverance in the Christian faith is rarely discussed by observers of the Hebrews. This paper describes how true Christian faith is always related to perseverance in the Christian faith. In this way, the debate about the concept of apostasy in Hebrews can be avoided. Through the exposition of Hebrews 12:1-3, it has been concluded that perfect faith is always followed by perseverance in faith.